Silicon-carbon negative electrode active material, and preparation method and application thereof

CN123017901APending Publication Date: 2026-10-30WANHUA CHEM GRP BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510549462.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但是,传统硅基材料的嵌锂机制为合金化过程,需要形成锂硅合金,在嵌锂后会发生巨大的体积膨胀,严重影响了锂离子电池的应用性能,这成为当前限制硅基材料大规模应用的主要障碍

Benefits of technology

[0051]本申请所述硅碳负极活性材料的数量密度粒度分布呈现双峰型,其中,粒度范围在[0.5μm,2.5μm]的X峰的面积SX与粒度范围在[1.5μm,15μm]的Y峰的面积SY的比例关系满足:5%≤SX/SY≤55%;尤其是结合限定所述硅碳负极活性材料的硅含量、比表面积和4MPa粉末电阻率参数,所述硅碳负极活性材料的颗粒间分布具有更适宜的兼容性,颗粒数量密度级配能够有效提高所述硅碳负极活性材料整体的体积能量密度,并有效降低了极片嵌锂时的膨胀率,使得复合材料整体的动力学性能也有了适当提升,可以兼顾低膨胀及快充性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017901A_ABST
    Figure CN123017901A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of secondary batteries, and particularly relates to a silicon-carbon negative electrode active material, and further discloses a preparation method thereof and application of the silicon-carbon negative electrode active material to preparation of a battery negative electrode sheet and a secondary battery. The number density particle size distribution of the silicon-carbon negative electrode active material is in a bimodal type, wherein the proportion relationship between the area S X of an X peak with a particle size range of [0.5 mu m, 2.5 mu m] and the area S Y of a Y peak with a particle size range of [1.5 mu m, 15 mu m] satisfies: 5% <= S X / S Y <= 55%. The inter-particle distribution of the silicon-carbon negative electrode active material has more suitable compatibility, the particle number density grading can effectively improve the volume energy density of the whole silicon-carbon negative electrode active material, and effectively reduces the expansion rate of the electrode sheet during lithium intercalation, so that the kinetics performance of the whole composite material is also properly improved, and the low expansion and fast charging performance can be considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of secondary battery technology, specifically relating to a silicon-carbon anode active material, and further disclosing its preparation method and its application in preparing battery anode sheets and secondary batteries. Background Technology

[0002] Lithium-ion batteries are energy storage devices widely used in energy storage, power batteries, and portable electronic devices. They have advantages such as high operating voltage, low self-discharge, and good safety. Lithium-ion batteries are mainly composed of positive electrode active materials, negative electrode active materials, electrolyte, separator, and casing. The negative electrode of a lithium battery is mainly made of a mixture of carbon or non-carbon materials, binders, and additives.

[0003] With the rapid development of industries such as new energy vehicles and low-altitude economy, lithium batteries are constantly moving towards higher energy density. The main path to this is through the use of positive and negative electrode active materials with higher specific capacity. However, due to the reduced safety of high specific capacity positive electrodes, the trend of high energy density of positive electrodes has encountered some setbacks. At present, improving the energy density of lithium batteries through negative electrodes has regained widespread attention.

[0004] Studies show that silicon-based materials, due to their advantages such as high theoretical specific capacity, low lithium intercalation potential, abundant reserves, and non-toxicity, have gradually moved from laboratory research to commercial application, becoming the preferred material to replace graphite in lithium-ion battery anode materials. However, the traditional lithium intercalation mechanism of silicon-based materials is an alloying process, requiring the formation of a lithium-silicon alloy. After lithium intercalation, a huge volume expansion occurs, severely affecting the application performance of lithium-ion batteries. This has become the main obstacle currently limiting the large-scale application of silicon-based materials. Summary of the Invention

[0005] This application provides a silicon-carbon anode active material, an anode sheet, and a secondary battery. The silicon-carbon anode active material combines low expansion and fast charging performance, effectively mitigating the volume expansion of the material and improving its cycle performance.

[0006] Firstly, this application provides a silicon-carbon anode active material, wherein the number density particle size distribution of the silicon-carbon anode active material exhibits a bimodal shape, wherein...

[0007] The area S of the X peak in the particle size range of [0.5 μm, 2.5 μm]. X The area S of the Y peak with a particle size range of [1.5 μm, 15 μm] Y The proportional relationship satisfies: 5% ≤ S X / S Y ≤55%, of which S X S refers to the peak area enclosed by the intersection of the X peak and the X-axis in the distribution curve obtained from particle size analysis. YIt refers to the peak area enclosed by the intersection of the Y peak and the X axis in the distribution curve obtained from particle size testing;

[0008] The silicon-carbon anode active material satisfies the following characteristics:

[0009] The silicon content (Si%) of the silicon-carbon anode active material satisfies: 45%wt ≤ Si% ≤ 50%wt; and / or,

[0010] The specific surface area S of the silicon-carbon anode active material bet ≤5m 2 / g; and / or,

[0011] The resistivity of the silicon-carbon anode active material at 4MPa is ≤100Ω·cm.

[0012] Particle size distribution (PSD) refers to the distribution of the number or mass of particles of different sizes in a given sample.

[0013] In one optional embodiment, the silicon-carbon anode active material satisfies the following characteristics:

[0014] The S X With S Y The proportional relationship satisfies: 20% ≤ S X / S Y ≤40%; and / or,

[0015] The silicon content (Si%) of the silicon-carbon anode active material satisfies: 46%wt ≤ Si% ≤ 49%wt; and / or,

[0016] The specific surface area S of the silicon-carbon anode active material bet ≤3m 2 / g; and / or,

[0017] The resistivity of the silicon-carbon anode active material at 4MPa is ≤50Ω·cm.

[0018] In one optional embodiment, the silicon-carbon anode active material comprises a mixture of first silicon-carbon particles and second silicon-carbon particles; wherein,

[0019] The first silicon-carbon particle satisfies: 5μm≤Dv50≤10μm, and particle size distribution span≤1.3;

[0020] The second silicon-carbon particle satisfies the following conditions: 0.5μm≤Dv50≤1.5μm, and particle size distribution span≤1.3.

[0021] In the silicon-carbon anode active material described in this application, it should be noted that Span is commonly used to evaluate the particle size distribution width, specifically the value calculated as (Dv90-Dv10) / Dv50. Here, Dv10 refers to the particle size corresponding to a cumulative volume distribution percentage of 10%, meaning that particles smaller than or equal to this size account for 10% of the total particle volume; Dv50 refers to the particle size corresponding to a cumulative volume distribution percentage of 50%, meaning that particles smaller than or equal to this size account for 50% of the total particle volume; and Dv90 refers to the particle size corresponding to a cumulative volume distribution percentage of 90%, meaning that particles smaller than or equal to this size account for 90% of the total particle volume. In the silicon-carbon anode active material described in this application, the parameters for the first and second silicon-carbon particles, including Dv50 and Span, are evaluated and calculated with reference to the above definitions.

[0022] In one optional embodiment, the mass ratio of the first silicon-carbon particles to the second silicon-carbon particles in the silicon-carbon anode active material is 2.5-15:1, wherein the optional range is 4-9:1.

[0023] In one optional embodiment, the silicon-carbon anode active material comprises a porous carbon matrix, wherein the first silicon-carbon particle and the second silicon-carbon particle are independently comprised of a silicon-carbon coating layer and a carbon coating layer sequentially coated on the surface of the porous carbon matrix.

[0024] Secondly, this application also provides a method for preparing the silicon-carbon anode active material, including a step of taking a selected amount of the first silicon-carbon particles and the second silicon-carbon particles and mixing them evenly.

[0025] Optionally, the method further includes the step of preparing the first silicon carbide particles and / or the second silicon carbide particles.

[0026] In one optional embodiment, in the method for preparing the silicon-carbon anode active material, the first silicon-carbon particles and the second silicon-carbon particles independently comprise a porous carbon matrix, and a silicon-carbon coating layer and a carbon coating layer sequentially coated on the surface of the porous carbon matrix.

[0027] The specific surface area of ​​the porous carbon substrate is 1500-1700 m². 2 / g, pore volume meets 0.7-0.8cm 3 / g, micropore ratio ≥80%;

[0028] Optionally, the particle size of the first porous carbon matrix forming the first silicon-carbon particles satisfies 5μm≤Dv50≤10μm and particle size distribution span≤1.3;

[0029] Optionally, the particle size of the second porous carbon matrix forming the second silicon-carbon particles satisfies 0.5μm≤Dv50≤1.5μm and particle size distribution span≤1.3.

[0030] In some embodiments, during the preparation of the silicon-carbon material, since the particle size and particle size distribution are inherited, the particle size of the porous carbon matrix corresponding to the first silicon-carbon particles is required to meet the following requirements: 5 μm ≤ Dv50 ≤ 10 μm, and particle size distribution span ≤ 1.3; the particle size of the porous carbon matrix corresponding to the second silicon-carbon particles is required to meet the following requirements: 0.5 μm ≤ Dv50 ≤ 1.5 μm, and particle size distribution span ≤ 1.3; in addition, the specific surface area of ​​the porous carbon substrate is required to be 1500–1700 m². 2 / g, pore volume meets 0.7~0.8cm 3 / g, micropores account for ≥80%.

[0031] In one optional embodiment, the method for preparing the first silicon carbide particles and / or the second silicon carbide particles includes vapor phase silicon deposition.

[0032] Optionally, the preparation steps of the first silicon-carbon particles and / or the second silicon-carbon particles, which are independent of each other, include the steps of taking a porous carbon matrix with a selected particle size distribution, sequentially performing silicon-carbon deposition to form the silicon-carbon coating layer, and performing carbon coating to form the carbon coating layer; wherein,

[0033] The silicon-carbon deposition step includes a step of passing the porous carbon matrix into a first gas phase containing silane gas for deposition; that is, a certain mass of porous carbon is usually placed in a fluidized bed reactor, and by controlling the deposition parameters, the silane gas in the first gas phase is adsorbed into the pores of the porous carbon and decomposed at high temperature to generate nano-silicon particles which are deposited into the pores of the porous carbon.

[0034] The carbon coating step includes passing the porous carbon matrix forming the silicon-carbon coating layer into a second gas phase containing acetylene gas for carbon coating; that is, the acetylene carbon coating reaction is usually carried out in a fluidized bed and a rotary kiln respectively.

[0035] Optionally, the silicon-carbon deposition step includes the following features:

[0036] The temperature within the reaction system is 400–600℃; and / or,

[0037] The fluidization velocity of the silane gas is 0.01-0.5 m / s;

[0038] The silane gas has a volume concentration of 5-50% based on the first gas phase;

[0039] The first gas phase also includes a protective gas; optionally, the protective gas may be nitrogen or an inert gas conventionally selected in the art.

[0040] Optionally, the carbon coating step includes the following features:

[0041] Control the reaction temperature to 600-800℃; and / or,

[0042] The acetylene gas concentration is 5-50% based on the volume concentration of the second gas phase;

[0043] The second gas phase also includes a protective gas; optionally, the protective gas may be nitrogen or an inert gas conventionally selected in the art.

[0044] Thirdly, this application also provides a negative electrode sheet, comprising:

[0045] Negative current collector, and

[0046] A negative electrode active material layer is disposed on at least one side of the negative electrode current collector;

[0047] The negative electrode active material layer includes the silicon-carbon negative electrode active material or the silicon-carbon negative electrode active material prepared by the method.

[0048] Fourthly, this application also provides a secondary battery, including the aforementioned negative electrode plate.

[0049] Fifthly, this application also provides an electrical device, including the aforementioned secondary battery.

[0050] The technical solution of this application has the following advantages:

[0051] The number density particle size distribution of the silicon-carbon anode active material described in this application exhibits a bimodal shape, wherein the area S of the X peak in the particle size range of [0.5 μm, 2.5 μm] is... X The area S of the Y peak with a particle size range of [1.5 μm, 15 μm] Y The proportional relationship satisfies: 5% ≤ S X / S Y ≤55%; In particular, combined with the limited silicon content, specific surface area and 4MPa powder resistivity parameters of the silicon-carbon anode active material, the interparticle distribution of the silicon-carbon anode active material has more suitable compatibility, the particle number density gradation can effectively improve the overall volumetric energy density of the silicon-carbon anode active material, and effectively reduce the expansion rate when the electrode is lithium intercalated, so that the overall dynamic performance of the composite material is also appropriately improved, and low expansion and fast charging performance can be taken into account.

[0052] The silicon-carbon anode active material described in this application, through the selection and blending of first and second silicon-carbon particles with appropriate particle size distributions and optimization of the particle size matching range, and with effective control of the blending ratio, allows the smaller-sized second silicon-carbon particles to fill the packing pores of the larger first silicon-carbon particles during the electrode rolling process by utilizing the interparticle slip effect. This effectively improves the overall volumetric energy density of the silicon-carbon anode active material. Simultaneously, these pores also provide space for the smaller second silicon-carbon particles to undergo a thixotropic reaction, mitigating volume changes and effectively reducing the expansion rate during electrode lithium intercalation. In particular, the smaller-sized second silicon-carbon particles, with their shorter lithium-ion diffusion paths, also appropriately improve the overall kinetic performance of the composite material, achieving a balance between low expansion and fast charging performance, thus greatly improving the application performance of the anode active material. Attached Figure Description

[0053] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0054] Figure 1 This is a particle size distribution diagram of the silicon-carbon anode active material prepared in Example 1 of this application;

[0055] Figure 2 This is a SEM image of silicon-carbon anode active material particles prepared in Example 1 of this application. Detailed Implementation

[0056] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0058] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0059] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0060] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0061] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0062] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).

[0063] Traditional silicon-based materials have advantages such as high theoretical specific capacity, low lithium intercalation potential, abundant reserves, and non-toxicity. However, because their lithium intercalation mechanism is an alloying process, it requires the formation of a lithium-silicon alloy. After lithium intercalation, a huge volume expansion occurs, which seriously affects the application performance of lithium-ion batteries.

[0064] To address the problems existing in the aforementioned related technologies, according to a first aspect of this application, a silicon-carbon anode active material is provided, wherein the number density particle size distribution of the silicon-carbon anode active material exhibits a bimodal shape, wherein...

[0065] The area S of the X peak in the particle size range of [0.5 μm, 2.5 μm]. X The area S of the Y peak with a particle size range of [1.5 μm, 15 μm] Y The proportional relationship satisfies: 5% ≤ S X / S Y ≤55%, of which S X S refers to the peak area enclosed by the intersection of the X peak and the X-axis in the distribution curve obtained from particle size analysis. Y It refers to the peak area enclosed by the intersection of the Y peak and the X axis in the distribution curve obtained from particle size testing;

[0066] The silicon-carbon anode active material satisfies the following characteristics:

[0067] The silicon content (Si%) of the silicon-carbon anode active material satisfies: 45%wt ≤ Si% ≤ 50%wt; and / or,

[0068] The specific surface area S of the silicon-carbon anode active material bet ≤5m 2 / g; and / or,

[0069] The resistivity of the silicon-carbon anode active material at 4MPa is ≤100Ω·cm.

[0070] The silicon-carbon anode active material described in this application effectively improves the overall volumetric energy density of the composite material by selecting first and second silicon-carbon particles with appropriate particle size distributions and optimizing the particle size matching range of the mixed particles. It also effectively reduces the expansion rate during lithium intercalation of the electrode, thereby appropriately improving the overall dynamic performance of the composite material and achieving a balance between low expansion and fast charging performance.

[0071] In some embodiments, the silicon-carbon anode active material, the S X With S Y The proportional relationship satisfies: 20% ≤ S X / S Y ≤40%.

[0072] In some embodiments, the silicon content (Si%) of the silicon-carbon anode active material satisfies: 46%wt ≤ Si% ≤ 49%wt.

[0073] In some embodiments, the specific surface area S of the silicon-carbon anode active material bet ≤3m 2 / g.

[0074] In some embodiments, the resistivity of the silicon-carbon anode active material at 4MPa is ≤50Ω·cm.

[0075] In some embodiments, the silicon-carbon anode active material comprises a mixture of first silicon-carbon particles and second silicon-carbon particles; wherein,

[0076] The silicon-carbon particle satisfies the following conditions: 5μm≤Dv50≤10μm, and particle size distribution span≤1.3;

[0077] The second silicon-carbon particle satisfies the following conditions: 0.5μm≤Dv50≤1.5μm, and particle size distribution span≤1.3.

[0078] In some embodiments, the Dv50 of the first silicon carbide particle is set to 5μm, 5.5μm, 6.0μm, 6.5μm, 7.0μm, 7.5μm, 8.0μm, 8.5μm, 9.0μm, 9.5μm, 10μm, or any value within the range of the above; and by adjusting the parameters of Dv10 and Dv90, the span calculation value is adjusted to 0.2, 0.3, 0.5, 0.6, 0.8, 1.0, 1.1, 1.2, 1.3, or any value within the range of the above.

[0079] In some embodiments, the Dv50 of the silicon carbide particles is set to 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, etc., or within any range of the above values; and by adjusting the parameters of Dv10 and Dv90, the span calculation value is adjusted to 0.2, 0.3, 0.5, 0.6, 0.8, 1.0, 1.1, 1.2, 1.3, etc., or within any range of the above values.

[0080] In the silicon-carbon anode active material described in this application, it should be noted that Span is commonly used to evaluate the particle size distribution width, specifically the value calculated as (Dv90-Dv10) / Dv50. Here, Dv10 refers to the particle size corresponding to a cumulative volume distribution percentage of 10%, meaning that particles smaller than or equal to this size account for 10% of the total particle volume; Dv50 refers to the particle size corresponding to a cumulative volume distribution percentage of 50%, meaning that particles smaller than or equal to this size account for 50% of the total particle volume; and Dv90 refers to the particle size corresponding to a cumulative volume distribution percentage of 90%, meaning that particles smaller than or equal to this size account for 90% of the total particle volume. In the silicon-carbon anode active material described in this application, the parameters of the first silicon-carbon particle and the second silicon-carbon particle are evaluated and calculated with reference to the above definitions for both Dv50 and Span.

[0081] In some embodiments, the mass ratio of the first silicon-carbon particles to the second silicon-carbon particles in the silicon-carbon anode active material is 2.5-15:1, wherein an optional range is 4-9:1.

[0082] In some embodiments, the silicon-carbon anode active material comprises, independently of each other, a porous carbon matrix, and a silicon-carbon coating layer and a carbon coating layer sequentially coated on the surface of the porous carbon matrix; wherein,

[0083] The specific surface area of ​​the porous carbon substrate is 1500-1700 m². 2 / g, pore volume meets 0.7-0.8cm 3 / g, micropores account for ≥80%.

[0084] In some embodiments, the specific surface area of ​​the porous carbon substrate is adjusted to meet the requirement of 1500-1700 m². 2 / g, for example, adjusting the specific surface area of ​​the porous carbon substrate to 1500, 1520, 1550, 1580, 1600, 1620, 1650, 1680, 1700 m². 2 / g, or within any of the above values.

[0085] In some embodiments, the pore volume of the porous carbon substrate is adjusted to meet the requirement of 0.7-0.8 cm³. 3 / g, for example, adjusting the pore volume of the porous carbon substrate to 0.7, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.8 cm³. 3 / g, or within any of the above values.

[0086] In some embodiments, the micropore ratio of the porous carbon substrate is adjusted to ≥80%, for example, the micropore ratio of the porous carbon substrate is adjusted to 80, 82, 84, 86, 88, 90, 92, 94, 95%, etc., or within any range of the above values.

[0087] Optionally, the particle size of the first porous carbon matrix forming the first silicon-carbon particles satisfies 5μm≤Dv50≤10μm and particle size distribution span≤1.3;

[0088] Optionally, the particle size of the second porous carbon matrix forming the second silicon-carbon particles satisfies 0.5μm≤Dv50≤1.5μm and particle size distribution span≤1.3.

[0089] Because the particle size and particle size distribution are inherited during the preparation of silicon-carbon materials, the particle size of the porous carbon matrix corresponding to the first silicon-carbon particles is required to satisfy 5μm≤Dv50≤10μm and the particle size distribution span≤1.3; the particle size of the porous carbon matrix corresponding to the second silicon-carbon particles is required to satisfy 0.5μm≤Dv50≤1.5μm and the particle size distribution span≤1.3. As an exemplary embodiment, the particle size Dv50 of the porous carbon matrix of the first silicon-carbon particles is controlled to be 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10μm, etc., or within any range of the above values; the span of the first silicon-carbon particles is controlled to be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, etc., or within any range of the above values. As an exemplary embodiment, the particle size Dv50 of the porous carbon matrix of the second silicon-carbon particles is controlled to be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 μm, or within any range of the above values; the span of the second silicon-carbon particles is controlled to be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, or within any range of the above values.

[0090] Secondly, this application also provides a method for preparing the silicon-carbon anode active material, including a step of uniformly mixing selected amounts of the first silicon-carbon particles and the second silicon-carbon particles.

[0091] In some embodiments, the method further includes the step of preparing the first silicon carbide particles and / or the second silicon carbide particles.

[0092] In some embodiments, the preparation method of the first silicon carbide particles and / or the second silicon carbide particles includes vapor phase deposition silicon method.

[0093] In some embodiments, the preparation steps of the first silicon-carbon particles and / or the second silicon-carbon particles independently include the steps of taking a porous carbon matrix with a selected particle size distribution, sequentially performing silicon-carbon deposition to form the silicon-carbon coating layer, and then performing carbon coating to form the carbon coating layer; wherein,

[0094] The silicon-carbon deposition step includes a step of passing the porous carbon matrix through a first gas phase containing at least silane gas for deposition.

[0095] The carbon coating step includes passing a porous carbon matrix forming the silicon-carbon coating layer through a second gas phase containing at least acetylene gas for carbon coating.

[0096] In some exemplary embodiments, the silicon-carbon deposition step includes the following features:

[0097] The temperature within the reaction system is 400–600℃, for example, adjusted to 400, 420, 450, 480, 500, 520, 550, 580, 600℃, or within any range of these values; and / or,

[0098] The fluidization velocity of the silane gas is 0.01-0.5 m / s. For example, the fluidization velocity of the silane gas can be adjusted to 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 m / s, or within any range of the above values.

[0099] The silane gas concentration is 5-50% based on the volume concentration of the first gas phase. For example, the volume concentration of the silane gas can be adjusted to 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 v / v%, or within any of the above values.

[0100] The first gas phase also includes a protective gas, such as nitrogen or an inert gas, and the volume concentration ratio of the two can be adjusted by adjusting the inlet flow rates of the silane gas and the protective gas.

[0101] In some exemplary embodiments, the carbon coating step includes the following features:

[0102] Control the reaction temperature to 600-800℃, for example, adjust the reaction temperature to 600, 620, 640, 660, 680, 700, 720, 740, 760, 780, 800℃, etc., or within any range of the above values; and / or,

[0103] The acetylene gas is controlled based on a volume concentration of 5-50% in the second gas phase. For example, the volume concentration of acetylene is adjusted to 5, 10, 15, 20, 25, 30, 35, 40, 45, 50%, or within any range of the above values.

[0104] The second gas phase also includes a protective gas, such as nitrogen or an inert gas, and the volume concentration ratio of the two can be adjusted by adjusting the inlet flow rates of the silane gas and the protective gas.

[0105] The preparation method of the silicon-carbon anode active material described in this application uses conventional materials in the field for both the first and second silicon-carbon particles. In this application, the difference in particle size between the first and second silicon-carbon particles mainly originates from the original particle size of the raw materials. The influence of the preparation process parameters on the particle size is very small. Therefore, within the limited process parameter range, the influence of the preparation process of the first and second silicon-carbon particles on their performance parameters and effects can be ignored.

[0106] As an exemplary embodiment, the preparation method of the silicon-carbon anode active material of this application includes the following steps:

[0107] (1) A porous carbon matrix with a suitable particle size distribution is first subjected to silane deposition in a fluidized bed to form a silicon-carbon coating layer on the surface of the porous carbon matrix; then it is fed into a rotary kiln for secondary carbon coating. The specific process is as follows: The preparation process usually involves first feeding porous carbon powder into a fluidized bed reactor, controlling the temperature of the reaction system at 400-600℃, the fluidizing gas velocity at 0.01-0.5m / s, adjusting the concentration of silane in the first gas phase to 5-50% (the remainder being protective gas), and controlling the ratio of the total mass of silane to the total mass of porous carbon within this range to 0.8-1.2. A silicon-carbon coating layer is formed on the surface of the substrate; then it is fed into a rotary kiln reactor for secondary carbon coating, and then acetylene gas is introduced for carbon coating. The concentration of the acetylene gas based on the second gas phase is 5-50% (the remainder is a protective gas). The preparation process usually involves transferring the above material into a rotary kiln reactor, controlling the reactor temperature at 600-800℃, adjusting the volume concentration of acetylene to 5-50%, and controlling the mass ratio of the total mass of acetylene introduced to the mass of the aforementioned product within this range to be 0.01-0.1, further forming a dense and complete carbon coating layer on its surface, resulting in first silicon-carbon particles with larger particle sizes.

[0108] (2) A porous carbon matrix with a suitable particle size distribution is first subjected to silane deposition in a fluidized bed to form a silicon-carbon coating layer on the surface of the porous carbon matrix; then it is fed into a rotary kiln for secondary carbon coating with acetylene. The specific process is as follows: The preparation process usually involves first feeding porous carbon powder into a fluidized bed reactor, controlling the temperature of the reaction system at 400-600℃, the fluidizing gas velocity at 0.01-0.5m / s, adjusting the volume concentration of silane in the first gas phase to 5-50% (the remainder being protective gas), and controlling the ratio of the total mass of silane to the total mass of porous carbon within this range to 0.8-1.2. A silicon-carbon coating layer is formed on the surface of a porous carbon matrix; then it is fed into a rotary kiln for secondary carbon coating, and then acetylene gas is introduced for carbon coating. The concentration of the acetylene gas based on the second gas phase is 5-50% (the remainder is a protective gas). The preparation process usually involves transferring the above material into a rotary kiln reactor, controlling the reactor temperature at 600-800℃, adjusting the volume concentration of acetylene gas to 5-50%, and controlling the mass ratio of the total mass of acetylene introduced to the mass of the aforementioned product within this range to be 0.01-0.1, further forming a dense and complete carbon coating layer on its surface, resulting in second silicon-carbon particles with smaller particle sizes.

[0109] (3) The first silicon carbon particles and the second silicon carbon particles are mixed in the selected mass ratio and thoroughly mixed to obtain the desired silicon carbon negative electrode active material.

[0110] Thirdly, this application also provides a negative electrode sheet, comprising:

[0111] Negative current collector, and

[0112] A negative electrode active material layer is disposed on at least one side of the negative electrode current collector;

[0113] The negative electrode active material layer includes the silicon-carbon negative electrode active material or the silicon-carbon negative electrode active material prepared by the method.

[0114] Fourthly, this application also provides a secondary battery, including the aforementioned negative electrode plate.

[0115] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.

[0116] The following uses a lithium-ion battery as an example to illustrate the secondary battery of this application.

[0117] [Positive electrode plate]

[0118] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material according to the first aspect of the present application.

[0119] As an example, the positive electrode current collector has two opposite surfaces in its own thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0120] The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may be selected from materials capable of absorbing and releasing lithium. The specific type of the positive electrode active material is not particularly limited and may be selected according to requirements, and the positive electrode active material described in the present application is selected from a lithium iron phosphate (LiFePO4) system. As an example, the positive electrode active material suitable for the battery system may include, but is not limited to, lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), lithium iron pyrophosphate (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel type lithium manganate (LiMn2O4), spinel type lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), layered lithium manganate (LiMnO2), lithium nickelate (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium magnesate (LiMgO2), lithium calciate (LiCaO2), lithium cuprate (LiCuO2), lithium zincate (LiZnO2), lithium molybdate (LiMoO2), lithium tantalate (LiTaO2), lithium tungstate (LiWO2), lithium nickel cobalt aluminum oxide (LiNi x Co y Al 1-x-y O2, 0<x<1, 0<y<1, 0<x+y<1, for example LiNi 0.8 Co 0.15 Al 0.05 O2), lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2, 0<x<1, 0<y<1, 0<x+y<1, for example LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1At least one of the following: O2, lithium-rich materials (e.g., lithium-rich nickel-cobalt-manganese oxide), manganese oxide (MnO2), vanadium oxide, sulfur oxide, silicate oxide, and their respective modified compounds. These materials may be used alone or in combination of two or more.

[0121] The modified compounds for the above-mentioned positive electrode active materials can be modified by doping, surface coating, or both doping and coating.

[0122] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0123] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0124] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0125] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0126] [Negative electrode plate]

[0127] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0128] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0129] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0130] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. The specific type of negative electrode active material is not specifically limited and can be selected according to requirements. For example, the negative electrode active material described in this application is a silicon-carbon material system. As an example, in addition to the negative electrode active material provided in this application, negative electrode active materials suitable for battery systems may also include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. These negative electrode active materials may be used alone or in combination of two or more.

[0131] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0132] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0133] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0134] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0135] [Electrolytes]

[0136] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0137] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0138] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0139] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0140] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0141] [Isolation membrane]

[0142] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0143] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0144] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0145] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0146] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0147] This application does not impose any particular restrictions on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape.

[0148] Fifthly, this application also provides an electrical device, including the secondary battery provided in the fourth aspect above.

[0149] In some embodiments, the aforementioned electrical device may also include a battery module or battery pack assembled from the aforementioned secondary batteries. The secondary batteries, battery modules, or battery packs can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0150] As the electrical device, a secondary battery, battery module, or battery pack can be selected according to its usage requirements. An example electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the secondary battery for this electrical device, a battery pack or battery module can be used.

[0151] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a rechargeable battery as their power source.

[0152] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0153] The preparation method of the silicon-carbon anode active material described in this application uses conventional materials in the art for both the first and second silicon-carbon particles. The following embodiments of this application, as an exemplary preparation method, include the following steps:

[0154] (1) Take porous carbon matrix with corresponding particle size distribution according to the selected particle size parameters (specific average value 1700 μm). 2 / g, average pore volume 0.8cm 3 / g, with an average micropore content of approximately 85%, silane is first deposited in a fluidized bed to form a silicon-carbon coating layer on the surface of the porous carbon matrix; then it is fed into a rotary kiln for secondary carbon coating. The specific process is as follows: The preparation process typically involves first placing 1.0 kg of porous carbon powder into a fluidized bed reactor, controlling the temperature of the reaction system at 500°C, the fluidizing gas velocity at 0.15 m / s, and controlling the concentration of silane in the first gas phase at 30% (the remainder being nitrogen) according to the silicon content requirements of the particulate material. Within this range, the ratio of the total mass of silane introduced to the total mass of porous carbon is controlled at 1.0. A silicon-carbon coating layer is formed on the surface of a porous carbon matrix; then it is fed into a rotary kiln reactor for secondary carbon coating, and then acetylene is introduced for deposition coating. The preparation process usually involves transferring the above material into a rotary kiln reactor, controlling the reactor temperature at 700°C, and controlling the concentration of acetylene in the second gas phase to 30% (the remainder being nitrogen) according to the parameter requirements of the particulate material. Within this range, the mass ratio of the total mass of acetylene introduced to the mass of the aforementioned product is controlled at 0.1, further forming a dense and complete carbon coating layer on its surface, obtaining first silicon-carbon particles with larger particle sizes, and measuring their Dv50 and span parameters.

[0155] (2) Take porous carbon matrix with corresponding particle size distribution according to the selected particle size parameters (average specific gravity 1700 μm). 2 / g, average pore volume 0.8cm 3 / g, with an average micropore content of approximately 85%, silane is first deposited in a fluidized bed to form a silicon-carbon coating layer on the surface of the porous carbon matrix; then it is fed into a rotary kiln for secondary acetylene carbon coating. The specific process is as follows: The preparation process typically involves first placing 1.0 kg of porous carbon powder into a fluidized bed reactor, controlling the temperature of the reaction system at 500°C, the fluidizing gas velocity at 0.1 m / s, and controlling the concentration of silane in the first gas phase at 30% (the remainder being nitrogen) according to the silicon content requirements of the particulate material. Within this range, the ratio of the total mass of silane introduced to the total mass of porous carbon is controlled at 1.0. A silicon-carbon coating layer is formed on the surface of a porous carbon matrix; then it is fed into a rotary kiln for secondary carbon coating, and then acetylene is introduced for deposition coating. The preparation process usually involves transferring the above material into a rotary kiln reactor, controlling the reactor temperature at 700°C, and controlling the concentration of acetylene in the second gas phase to 30% (the remainder being nitrogen) according to the parameter requirements of the particulate material. Within this range, the mass ratio of the total mass of acetylene introduced to the mass of the aforementioned product is controlled at 0.05, further forming a dense and complete carbon coating layer on its surface, obtaining second silicon-carbon particles with smaller particle size, and measuring their Dv50 and span parameters.

[0156] (3) The first silicon carbon particles and the second silicon carbon particles are mixed in the selected mass ratio and thoroughly mixed to obtain the desired silicon carbon negative electrode active material.

[0157] In the following embodiments of this application, the powder resistivity test at 4 MPa is performed in accordance with the powder resistivity test method in GB / T 30835-2014 standard.

[0158] In the following embodiments of this application, the first silicon-carbon particles and the second silicon-carbon particles prepared by the above method are used as examples to illustrate the influence of particle ratio on the overall performance of the negative electrode material. However, the effects of the first silicon-carbon particles and the second silicon-carbon particles prepared by other conventional methods and parameters in the art are no different.

[0159] Example 1

[0160] In the silicon-carbon anode active material described in this embodiment:

[0161] The first silicon-carbon particle has a Dv50 of 8.15 μm and a particle size distribution span of 1.17.

[0162] The second silicon-carbon particle has a Dv50 of 1.03 μm and a particle size distribution span of 1.26.

[0163] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 6.5:1.

[0164] The particle size distribution diagram of the silicon-carbon anode active material prepared in this embodiment is shown in the appendix. Figure 1 As can be seen, its quantity density distribution exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5μm, 2.5μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) y The ratio S X / S Y =35%.

[0165] SEM images of the silicon-carbon anode active material particles prepared in this embodiment are attached. Figure 2 .

[0166] Measurements showed that the silicon content (Si%) of the silicon-carbon anode active material prepared in this embodiment was 48.5%, and the specific surface area (S) was... bet It is 1.98m 2 / g, 4MPa powder resistivity 23.5Ω·cm.

[0167] Example 2

[0168] In the silicon-carbon anode active material described in this embodiment:

[0169] The first silicon-carbon particle has a Dv50 of 5.0 μm and a particle size distribution span of 1.2.

[0170] The second silicon-carbon particle has a Dv50 of 0.8 μm and a particle size distribution span of 1.2.

[0171] The mass ratio of the first silicon-carbon particle to the second silicon-carbon particle is 11:1.

[0172] The number density distribution of the silicon-carbon anode active material prepared in this embodiment exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) Y The ratio S X / S Y =10%.

[0173] Measurements showed that the silicon content (Si%) of the silicon-carbon anode active material prepared in this embodiment was 47.8%, and the specific surface area (S) was... bet It is 2.03m 2 / g, the resistivity of the powder at 4MPa is 16.8Ω·cm.

[0174] Example 3

[0175] In the silicon-carbon anode active material described in this embodiment:

[0176] The first silicon-carbon particle has a Dv50 of 6.0 μm and a particle size distribution span of 1.15.

[0177] The second silicon-carbon particle has a Dv50 of 1.4 μm and a particle size distribution span of 1.15.

[0178] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 4:1.

[0179] The number density distribution of the silicon-carbon anode active material prepared in this embodiment exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) Y The ratio S X / S Y =50%.

[0180] Measurements showed that the silicon content (Si%) of the silicon-carbon anode active material prepared in this embodiment was 48.9%, and the specific surface area (S) was... bet It is 1.24m 2 / g, the resistivity of the powder at 4MPa is 38.5Ω·cm.

[0181] Example 4

[0182] In the silicon-carbon anode active material described in this embodiment:

[0183] The first silicon-carbon particle has a Dv50 of 7.2 μm and a particle size distribution span of 1.2.

[0184] The second silicon-carbon particle has a Dv50 of 1.35 μm and a particle size distribution span of 1.1.

[0185] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 2.5:1.

[0186] The number density distribution of the silicon-carbon anode active material prepared in this embodiment exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) Y The ratio S X / S Y =55%.

[0187] Measurements showed that the silicon content (Si%) of the silicon-carbon anode active material prepared in this embodiment was 48.3%, and the specific surface area (S) was... bet It is 2.88m 2 / g, the resistivity of the powder at 4MPa is 47.9Ω·cm.

[0188] Example 5

[0189] In the silicon-carbon anode active material described in this embodiment:

[0190] The first silicon-carbon particle has a Dv50 of 8.5 μm and a particle size distribution span of 1.12.

[0191] The second silicon-carbon particle has a Dv50 of 1.2 μm and a particle size distribution span of 1.08.

[0192] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 9:1.

[0193] The number density distribution of the silicon-carbon anode active material prepared in this embodiment exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) Y The ratio S X / S Y =20%.

[0194] Measurements showed that the silicon content (Si%) of the silicon-carbon anode active material prepared in this embodiment was 45.8%, and the specific surface area (Sbet) was 3.96 m².2 / g, the resistivity of the powder at 4MPa is 7.63Ω·cm.

[0195] Example 6

[0196] In the silicon-carbon anode active material described in this embodiment:

[0197] The first silicon-carbon particle has a Dv50 of 9.4 μm and a particle size distribution span of 0.98.

[0198] The second silicon-carbon particle has a Dv50 of 1.05 μm and a particle size distribution span of 1.03.

[0199] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 15:1.

[0200] The number density distribution of the silicon-carbon anode active material prepared in this embodiment exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) Y The ratio S X / S Y =5%.

[0201] Measurements showed that the silicon content (Si%) of the silicon-carbon anode active material prepared in this embodiment was 49.4%, and the specific surface area (Sbet) was 1.29 m². 2 / g, the resistivity of the powder at 4MPa is 66.2Ω·cm.

[0202] Example 7

[0203] In the silicon-carbon anode active material described in this embodiment:

[0204] The first silicon-carbon particle has a Dv50 of 6.08 μm and a particle size distribution span of 1.26.

[0205] The second silicon-carbon particle has a Dv50 of 0.80 μm and a particle size distribution span of 1.26.

[0206] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 5:1.

[0207] The number density distribution of the silicon-carbon anode active material prepared in this embodiment exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) y The ratio S X / S Y =40%.

[0208] Measurements showed that the silicon content (Si%) of the silicon-carbon anode active material prepared in this embodiment was 48.1%, and the specific surface area (S) was... bet It is 1.78m 2 / g, the resistivity of the powder at 4MPa is 15.3Ω·cm.

[0209] Comparative Example 1

[0210] The preparation method of the silicon-carbon anode active material described in this comparative example is the same as that in Example 1, except that:

[0211] The first silicon-carbon particle has a Dv50 of 6.08 μm and a particle size distribution span of 1.04.

[0212] The second silicon-carbon particle has a Dv50 of 0.80 μm and a particle size distribution span of 1.58.

[0213] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 4:1.

[0214] The number density distribution of the silicon-carbon anode active material prepared in this embodiment exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) Y The ratio S X / S Y =70%.

[0215] Comparative Example 2

[0216] The preparation method of the silicon-carbon anode active material described in this comparative example is the same as that in Example 1, except that:

[0217] The first silicon-carbon particle has a Dv50 of 6.08 μm and a particle size distribution span of 1.58.

[0218] The second silicon-carbon particle has a Dv50 of 0.80 μm and a particle size distribution span of 1.04.

[0219] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 8:1.

[0220] The number density distribution of the silicon-carbon anode active material prepared in this comparative example exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) y The ratio S X / S Y =60%.

[0221] Comparative Example 3

[0222] The preparation method of the silicon-carbon anode active material described in this comparative example is the same as that in Example 1, except that:

[0223] The first silicon-carbon particle has a Dv50 of 11.0 μm and a particle size distribution span of 1.26.

[0224] The second silicon-carbon particle has a Dv50 of 0.3 μm and a particle size distribution span of 1.26.

[0225] The mass ratio of the first silicon-carbon particle to the second silicon-carbon particle is 6:1.

[0226] The number density distribution of the silicon-carbon anode active material prepared in this comparative example exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) y The ratio S X / S Y =65%.

[0227] Comparative Example 4

[0228] The preparation method of the silicon-carbon anode active material described in this comparative example is the same as that in Example 1, except that:

[0229] The first silicon-carbon particle has a Dv50 of 4.4 μm and a particle size distribution span of 1.26.

[0230] The second silicon-carbon particle has a Dv50 of 1.65 μm and a particle size distribution span of 1.26.

[0231] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 7:1.

[0232] The number density distribution of the silicon-carbon anode active material prepared in this comparative example exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) y The ratio S X / S Y =90%.

[0233] Comparative Example 5

[0234] The preparation method of the silicon-carbon anode active material described in this comparative example is the same as that in Example 1, except that:

[0235] The first silicon-carbon particle has a Dv50 of 11.4 μm and a particle size distribution span of 1.45.

[0236] The second silicon-carbon particle has a Dv50 of 1.65 μm and a particle size distribution span of 1.45.

[0237] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 9:1.

[0238] The number density distribution of the silicon-carbon anode active material prepared in this comparative example exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) y The ratio S X / S Y =75%.

[0239] Comparative Example 6

[0240] The preparation method of the silicon-carbon anode active material described in this comparative example is the same as that in Example 1, except that:

[0241] The first silicon-carbon particle has a Dv50 of 4.0 μm and a particle size distribution span of 1.45.

[0242] The second silicon-carbon particle has a Dv50 of 0.45 μm and a particle size distribution span of 1.45.

[0243] The mass ratio of the first silicon-carbon particles to the second silicon-carbon particles is 5:1.

[0244] The number density distribution of the silicon-carbon anode active material prepared in this comparative example exhibits a bimodal shape, with the area S of peak X (the particle size range of peak X is [0.5 μm, 2.5 μm]) being... x The area S of peak Y (the particle size range of Y peak is [1.5 μm, 15 μm]) y The ratio S X / S Y =115%.

[0245] Test case

[0246] 1. Physical and chemical performance testing

[0247] In the following test examples of this application, the physical parameters of the silicon-carbon anode active materials prepared according to the schemes in Examples 1-8 and Comparative Examples 1-7 were measured. The specific test indicators and methods are as follows.

[0248] Tap density: The tap density was determined according to the test method described in the national standard GB / T 24533 for graphite anode materials of lithium-ion batteries.

[0249] Compacted density: The compacted density was determined according to the test method for powder compaction described in the national standard GB / T 24533 Graphite Anode Materials for Lithium-ion Batteries.

[0250] In this test example, the physicochemical performance parameters of the silicon-carbon anode active materials prepared by each embodiment and comparative scheme are shown in Table 1 below.

[0251] Table 1. Results of physicochemical performance tests

[0252] serial number <![CDATA[Tap density g / cm 3 > <![CDATA[Compaction density g / cm 3 > Example 1 0.97 1.00 Example 2 0.98 1.01 Example 3 0.96 0.99 Example 4 0.97 1.00 Example 5 0.98 1.01 Example 6 0.96 0.99 Example 7 0.97 1.00 Comparative Example 1 0.93 0.94 Comparative Example 2 0.92 0.93 Comparative Example 3 0.91 0.92 Comparative Example 4 0.93 0.94 Comparative Example 5 0.92 0.93 Comparative Example 6 0.91 0.92

[0253] As can be seen, the number density particle size distribution of the silicon-carbon anode active material described in this application exhibits a bimodal shape, wherein the area S of the X peak in the particle size range of [0.5 μm, 2.5 μm] is... X The area S of the Y peak with a particle size range of [1.5 μm, 15 μm] Y The proportional relationship satisfies: 5% ≤ S X / S Y ≤55%, of which S X S refers to the peak area enclosed by the intersection of the X peak and the X-axis in the distribution curve obtained from particle size analysis. Y This refers to the peak area enclosed by the intersection of the Y-peak and the X-axis in the distribution curve obtained from particle size testing. When the silicon-carbon anode active material possesses the above characteristics, there is better compatibility between particles, good particle size matching between large-sized particles and graphite particles, and small-sized particles can fill the gaps in graphite particles and larger silicon-carbon particles very well, giving it high tap density and high pressure tap density characteristics. In addition, the second silicon-carbon particles with small particle size can fill the packing pores of the large first silicon-carbon particles during the electrode rolling process by utilizing the particle slip effect, effectively improving the overall volumetric energy density of the composite material. However, in the schemes of Comparative Examples 1-6, adjusting either the Dv50 or span value of the first and / or second silicon-carbon particles will affect the S of the mixed silicon-carbon anode material. X / S Y The ratio affects the spatial matching between the first and second silicon carbide particles, and also affects the tap density and compaction density of the material.

[0254] 2. Electrochemical performance testing

[0255] In the following test examples of this application, the electrochemical performance of silicon-carbon anode active materials prepared according to the schemes in Examples 1-8 and Comparative Examples 1-7 was measured. The specific test indicators and methods are as follows.

[0256] Coin cell full capacity test: The silicon-carbon anode active material and graphite material were mixed at a mass ratio of 1:4. The mixed material was used as the anode. The cathode was a high-nickel ternary material Ni83 system. The electrolyte system was a conventional EC / EMC / DMC (1:1:1, v / v / v), 1M LiPF6, and 5% FEC (fluoroethylene carbonate) was added. Coin cells were prepared according to the coin cell manufacturing method and tested with a charge and discharge current of 0.1C.

[0257] Full-charge expansion rate: The button cell that has undergone charge-discharge testing is disassembled, the negative electrode is removed, and the residual electrolyte on the electrode surface is washed away with an organic solvent. The original electrode thickness is compared, and the change in electrode thickness after charging is measured to calculate the expansion rate. Expansion rate calculation formula = (Electrode thickness after charging - Original electrode thickness) / (Original electrode thickness - Foil thickness) * 100%.

[0258] 0.1C / 2C charge retention rate: First, perform the first charge and discharge of the above button cell, and then perform a high-rate 2C charge. The charge retention rate is calculated as follows: 2C charge capacity / 0.1C charge capacity * 100%.

[0259] In this test example, the electrochemical performance parameters of the batteries corresponding to the silicon-carbon anode active materials prepared by each embodiment and comparative scheme are shown in Table 2 below.

[0260] Table 2 Electrochemical performance test results

[0261]

[0262] As can be seen, the number density particle size distribution of the silicon-carbon anode active material described in this application exhibits a bimodal shape, wherein the area S of the X peak in the particle size range of [0.5 μm, 2.5 μm] is... X The area S of the Y peak with a particle size range of [1.5 μm, 15 μm] Y The proportional relationship satisfies: 5% ≤ S X / S Y ≤55%, of which S X S refers to the peak area enclosed by the intersection of the X peak and the X-axis in the distribution curve obtained from particle size analysis. YThis refers to the peak area enclosed by the intersection of the Y-peak and the X-axis in the distribution curve obtained from particle size testing. When the silicon-carbon anode active material possesses the above characteristics, the particles exhibit better compatibility, with good particle size matching between large-sized particles and graphite particles. Simultaneously, small-sized particles can fill the gaps between graphite particles and larger silicon-carbon particles very well, enabling them to achieve higher capacity utilization. The silicon-carbon particles, with the help of the elastic matrix of graphite, greatly limit particle expansion. At the same time, the good electrical contact between particles results in a higher high-rate discharge retention rate. Furthermore, these pores also provide space for the small-sized second silicon-carbon particles to undergo a lithiation reaction, effectively reducing the expansion rate during electrode lithium intercalation. In particular, the small-diameter second silicon-carbon particles, with their shorter lithium-ion diffusion path, also appropriately improve the overall kinetic performance of the composite material, achieving a balance between low expansion and fast charging performance, greatly improving the application performance of the anode active material.

[0263] In contrast to the schemes in Examples 1-6, adjusting either the Dv50 or span value of the first and / or second silicon-carbon particles will affect the S of the mixed silicon-carbon anode material. X / S Y The ratio affects the spatial matching between the first and second silicon-carbon particles, and also affects the electrochemical performance of the material.

[0264] In summary, the number density particle size distribution of the silicon-carbon anode active material of this application exhibits a bimodal shape, wherein the area S of the X peak in the particle size range of [0.5 μm, 2.5 μm] is... X The area S of the Y peak with a particle size range of [1.5 μm, 15 μm] Y The proportional relationship satisfies: 5% ≤ S X / S Y ≤55%. The silicon-carbon anode active material described in this application, by selecting first and second silicon-carbon particles with appropriate particle size distributions for mixing and optimizing the particle size matching range of the mixed particles, effectively improves the overall volumetric energy density of the composite material and effectively reduces the expansion rate during lithium intercalation of the electrode, thereby appropriately improving the overall kinetic performance of the composite material and achieving a balance between low expansion and fast charging performance.

[0265] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this application.

Claims

1. A silicon-carbon anode active material, characterized in that, The number density particle size distribution of the silicon-carbon anode active material exhibits a bimodal shape, wherein the area S of the X peak in the particle size range of [0.5 μm, 2.5 μm] is... X The area S of the Y peak with a particle size range of [1.5 μm, 15 μm] Y The proportional relationship satisfies: 5% ≤ S X / S Y ≤55%, of which S X S refers to the peak area enclosed by the intersection of the X peak and the X-axis in the distribution curve obtained from particle size analysis. Y It refers to the peak area enclosed by the intersection of the Y peak and the X axis in the distribution curve obtained from particle size testing; The silicon-carbon anode active material satisfies the following characteristics: The silicon content (Si%) of the silicon-carbon anode active material satisfies: 45%wt ≤ Si% ≤ 50%wt; and / or, The specific surface area S of the silicon-carbon anode active material bet ≤5m 2 / g; and / or, The resistivity of the silicon-carbon anode active material at 4MPa is ≤100Ω·cm.

2. The silicon-carbon anode active material according to claim 1, characterized in that, The silicon-carbon anode active material satisfies the following characteristics: The S X With S Y The proportional relationship satisfies: 20% ≤ S X / S Y ≤40%; and / or, The silicon content (Si%) of the silicon-carbon anode active material satisfies: 46%wt ≤ Si% ≤ 49%wt; and / or, The specific surface area S of the silicon-carbon anode active material bet ≤3m 2 / g; and / or, The resistivity of the silicon-carbon anode active material at 4MPa is ≤50Ω·cm.

3. The silicon-carbon anode active material according to claim 1 or 2, characterized in that, The silicon-carbon anode active material comprises a mixture of first silicon-carbon particles and second silicon-carbon particles; wherein, The first silicon-carbon particle satisfies: 5μm≤Dv50≤10μm, and particle size distribution span≤1.3; The second silicon-carbon particle satisfies the following conditions: 0.5μm≤Dv50≤1.5μm, and particle size distribution span≤1.

3.

4. The silicon-carbon anode active material according to claim 3, characterized in that, The mass ratio of the first silicon carbide particle to the second silicon carbide particle is 2.5-15:1, and the optional mass ratio is 4-9:

1.

5. The silicon-carbon anode active material according to any one of claims 1-4, characterized in that, The first silicon-carbon particle and the second silicon-carbon particle each independently comprise a porous carbon matrix, and a silicon-carbon coating layer and a carbon coating layer sequentially coated on the surface of the porous carbon matrix.

6. A method for preparing the silicon-carbon anode active material as described in any one of claims 1-5, characterized in that, The process includes the step of taking a selected amount of first silicon carbide particles and second silicon carbide particles and mixing them evenly. Optionally, the method further includes the step of preparing the first silicon carbide particles and / or the second silicon carbide particles; Optionally, the first silicon-carbon particle and the second silicon-carbon particle independently comprise a porous carbon matrix, and a silicon-carbon coating layer and a carbon coating layer sequentially coated on the surface of the porous carbon matrix; Optionally, the specific surface area of ​​the porous carbon substrate is 1500-1700 m². 2 / g, pore volume meets 0.7-0.8cm 3 / g, micropore ratio ≥80%; Optionally, the particle size of the first porous carbon matrix forming the first silicon-carbon particles satisfies 5μm≤Dv50≤10μm and particle size distribution span≤1.3; Optionally, the particle size of the second porous carbon matrix forming the second silicon-carbon particles satisfies 0.5μm≤Dv50≤1.5μm and particle size distribution span≤1.

3.

7. The method for preparing the silicon-carbon anode active material according to claim 6, characterized in that, The preparation method of the first silicon-carbon particles and / or the second silicon-carbon particles includes vapor phase precipitation silicon method; Optionally, the preparation steps of the first silicon-carbon particles and / or the second silicon-carbon particles, which are independent of each other, include the step of taking the porous carbon matrix with a selected particle size distribution, sequentially performing silicon-carbon deposition to form the silicon-carbon coating layer, and the step of performing carbon coating to form the carbon coating layer; wherein, The silicon-carbon deposition step includes a step of passing the porous carbon matrix through a first gas phase containing silane gas for deposition. The carbon coating step includes passing a porous carbon matrix forming the silicon-carbon coating layer through a second gas phase containing acetylene gas for carbon coating. Optionally, the silicon-carbon deposition step includes the following features: The temperature within the reaction system is 400–600℃; and / or, The fluidization velocity of the silane gas is 0.01-0.5 m / s; The silane gas has a volume concentration of 5-50% based on the first gas phase; The first gas phase also includes a protective gas; Optionally, the carbon coating step includes the following features: Control the reaction temperature to 600-800℃; and / or, The acetylene gas has a volume concentration of 5-50% based on the second gas phase; The second gas phase also includes a protective gas.

8. A negative electrode sheet, characterized in that, include: Negative current collector, and A negative electrode active material layer is disposed on at least one side of the negative electrode current collector; The negative electrode active material layer comprises the silicon-carbon negative electrode active material according to any one of claims 1-5 or the silicon-carbon negative electrode active material prepared by the method according to claim 6 or 7.

9. A secondary battery, characterized in that, Includes the negative electrode sheet as described in claim 8.

10. An electrical device, characterized in that, Includes the secondary battery as described in claim 9.